1977
DOI: 10.1007/bf00499929
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of sodium and water through isolated rat colonic mucosa under the influence of deoxycholate and oxyphenisatin

Abstract: 1. The influence of oxyphenisatin (OP), a diphenolic laxative, and deoxycholate (DC) on the transfer of sodium and water in an everted sac preparation of stripped rat colon was investigated. 2. OP (10(-5) M, mucosal side) and DC (3 X 10(-4) M, mucosal side) completely blocked net water and sodium absorption. Net movements from the serosal to the mucosal side could not be induced by higher concentrations of the drugs. 3. Unidirectional sodium movements in both directions were increased by OP and DC. 4. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…These data indicate that DOC stimulates an active transcellular secretory process, such as is observed with other laxatives, e.g. bisacodil or phenolphthalein, which raise cyclic AMP within colonic mucosa and increase K+ conductance across the apical membrane (Conley et al 1976;Wanitschke et al 1977;Freel et al 1983a, b;Smith & McCabe, 1984). DOC reduces the colonic suction capacity, as demonstrated by the rise in the ratio of absorbate hypertonicity/gel suction pressure.…”
Section: Effects Of Luminal Hydraulic Resistance On Water and Ionic Amentioning
confidence: 75%
See 1 more Smart Citation
“…These data indicate that DOC stimulates an active transcellular secretory process, such as is observed with other laxatives, e.g. bisacodil or phenolphthalein, which raise cyclic AMP within colonic mucosa and increase K+ conductance across the apical membrane (Conley et al 1976;Wanitschke et al 1977;Freel et al 1983a, b;Smith & McCabe, 1984). DOC reduces the colonic suction capacity, as demonstrated by the rise in the ratio of absorbate hypertonicity/gel suction pressure.…”
Section: Effects Of Luminal Hydraulic Resistance On Water and Ionic Amentioning
confidence: 75%
“…DOC inhibits normal colonic fluid and electrolyte absorption by disruption of tight junctions, thereby increasing paracellular permeability (Freel, Hatch, Earnest & Goldner, 1983a, b;Bleakman & Naftalin, 1990). It also stimulates adenylate cyclase activity, thereby raising K+ conductance of the apical membrane and thus inducing active K+ secretion into the colonic lumen (Conley, Coyne, Bonnoris, Chung & Schoenfeld, 1976;Wanitschke, Nell, Rummel & Specht, 1977;Freel et al 1983a, b;Smith & McCabe, 1984). PEG 4000 (10 mM) has a high osmotic coefficient and exerts an osmotic pressure of ca 15 mosmol kg' (Naftalin & Tripathi, 1985).…”
Section: P S Zammit M Mendizabal and R J Naftalinmentioning
confidence: 99%
“…This secretion process has been interpreted as an active one (4), but seems unlikely in view of the results of Ewe (8). Active secretion could be the result of an increased hydraulic permeabil ity of the colonic epithelium (28,29). The fluid which appeared in the everted sac method on the mucosal side is isotonic.…”
Section: Discussionmentioning
confidence: 99%
“…In a parallel paper [ 12] it is shown that the secreted fluid volume dur ing perfusion of the rat colon with deoxycho late is quantitatively determined by increased mucosal permeability. Gross epithelial dam age with disruption of the epithelium and exposure of the underlying basal membrane Deoxycholate 6 in vivo rabbit [3] Deoxycholatc 0.3 in vitro rat [4] Deoxycholatc 0.3-1.0 in vitro rat [5] Deoxycholate 5 in vivo rabbit [6] Dioctyl sodium sulphosuccinate 0.5-2.0 in vivo rat [7] Ricinoleate 2.5-10 in vivo rabbit [8] has been claimed to be responsible for this increased permeability [3], However, in the parallel paper [12] it was shown that even a dramatic increase in epithelial permeability was reversible and returned to normal values after 2 h, an argument against epithelial ero sions or ulcers. Therefore, in parallel to the study on the effect on fluid and electrolyte transfer and intestinal permeability, we car ried out a scanning and transmission elec tron-microscopic study on the effect of deoxycholate on the colonic epithelium.…”
mentioning
confidence: 99%